Investigation Effort of the Surakarta Police Criminal Investigation Bureau in Disclosure of the Crime of Vehicle Theft to Increase Crime Clearance - Haidar Fadhil Lubis (Advances in Police Science Research Journal, 2022)
This research is motivated by data on the increase in the number of criminal acts by the Surakarta Police, accompanied by a decrease in the settlement of criminal acts of vehicle theft in the last 3 years. The National Police has the task of enforcing the law based on Law Number 2 of 2002 concerning the Indonesian National Police, which is carried out by the technical function of Criminal Investigation. This study aims to determine the implementation of the Surakarta Police Criminal Investigation Bureau in the disclosure of theft crimes in order to increase crime clearance, and the Surakarta Police Criminal Investigation Bureau efforts in the disclosure of theft crimes in order to increase crime clearance. To process the data, the authors use management theory as well as concepts and laws governing the procedures for conducting criminal investigations. This research was conducted with a qualitative approach, the type of action research and data collection techniques with interviews, observations, and document studies. The results showed that the main obstacle in carrying out the investigation of the crime of theft was the perpetrators who carried away evidence, and the investigation efforts carried out by the Surakarta Police Criminal Investigastion Bureau were not optimal in order to increase crime clearance. This is influenced by several factors, namely internal and external factors of the organization. Internally, the organization has increased budget plans and methods that are in accordance with laws and regulations as supporting factors and human resources and inadequate facilities and infrastructure as inhibiting factors. Meanwhile, externally, namely the facilities at the crime scene as supporting factors and difficult evidence, the way of the perpetrators, and the reporting party unable to show proof of ownership as inhibiting factors. Based on the results of the study, the authors suggest empowering personnel, budget support as well as facilities and infrastructure from the National Police, collaboration with internal and external parties, innovations in vehicle tracking devices, and the use of the latest technology to help track down perpetrators and evidence.